How leaf rust disease and its control with fungicides affect dough properties, gluten quality and loaf volume under different N rates in wheat. (March 2018) - Fleitas, María Constanza; Schierenbeck, Matías; Gerard, Guillermo Sebastián; Dietz, Juan Ignacio; Golik, Silvina Inés; Campos, Pablo Eduardo; Simón, María Rosa
Abstract: The unique viscoelastic properties of gluten make bread wheat ( Triticum aestivum L.) a staple food. The specific balance between gluten fractions, together with grain protein content (GPC), defines nutritional and end-use properties. The leaf rust ( Puccinia triticina Eriks.) and its control using succinate dehydrogenase inhibitors (SDHIs) fungicides together with nitrogen (N) fertilization could alter the GPC and its composition during the grain-filling period, modifying dough properties. The aim of this study was to investigate the effects of leaf rust, its control using fluxapyroxad (SDHI) and the interaction with N fertilization on breadmaking quality of wheat. Two field experiments were conducted during 2014 and 2015 in a split-split plot design with three fungicide treatments as main plots and three N fertilization rates as subplots using a susceptible cultivar. Leaf rust reduced GPC and modified its composition. The disease shortened the grain-filling period and reduced gluten content. Gluten tenacity (Alv P ) was more affected than gluten extensibility (Alv L ) resulting in doughs with lower Alv P / L ratio, minor gluten strength and inferior loaf volume. The treatment containing fluxapyroxad showed better levels of disease control and it also evidenced additional beneficial effects in most of the evaluated parameters compared to the treatment without this active ingredient. Highlights: Leaf rust effect (biotic stress) on dough rheology and breadmaking quality of wheat is addressed. Grain protein content and gluten content decreased in rusted plants compared to protected ones. Dough tenacity (alveogram P ) was more affected than dough extensibility (alveogram L ). The fungicide containing the SDHI fluxapyroxad extended green canopy life. Breadmaking parameters improved after fungicide applications and N fertilization.